Macroscopic study of waste management by domestic consumer - Muhammad Syamim , Hisham (2013)
Solid waste generation in Malaysia is currently at an alarming situation. There is an issue on how the government and consumers manage their discarded waste nationally and small clusters. This study is about solid waste management among Malaysian society. The focus areas for this study is in the district of Kiantan, Pahang. With regard to the three types of the low-cost housing, moderate residential area and high-class areas, the comparison of waste management has been made. The purpose of this study is to fmd out how people in Kuantan manage waste generated, measure the weight of each type of waste that has been generated, comparing the waste generated in Kuantan with other big cities around Malaysia, and make observations regarding waste storage systems in every selected residential area. This study shows that food waste is the highest type of waste generated by the residents in every city. In addition, the waste storage system who applied in the study area is relatively good level because every house provides the garbage container in front of the house. The waste management by domestic consumers in all the study area is still at low level because no one of them show clear evidence for separation of waste produce.